Video Animasi Pencegahan Penularan HIV dari Ibu ke Anak (PPIA) terhadap Pengetahuan Ibu Hamil - Kadek Indah Shanti Devi; Intan Gumilang Pratiwi; Lina Sundayani; Fitra Arsy Nur Cory’ah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2026)
World Health Organization data (2023) shows that there are 1.2 million pregnant women living with HIV. Ministry of Health data (2023) shows an increase in HIV cases in Indonesia of 0.3% are pregnant women. According to 2023 data, KPAP NTB recorded that there were 66 cases of HIV/AIDS found. According to KPA Lobar in 2023, there were three pregnant women diagnosed with HIV. Data from the Sedau Community Health Center (UPT) in September 2024 showed that 1 pregnant woman was detected with HIV. Seeing the increase in cases, a national response is needed with the PPIA Program. Based on a preliminary survey, 4 pregnant women did not understand about PPIA and had not received information about PPIA. To determine the effect of animated videos about the PPIA program on the knowledge of pregnant women in Keru Village, the working area of ​​the Sedau Community Health Center (UPT). The type of research is Quasi Experiment Nonequivalent Control Group Design, with a Total sampling technique. The population of this study. Researchers took all samples, namely 66 pregnant women. Data analysis Independent t-test. The average knowledge before the intervention using the PPIA Animation Video was 65.28 and after it became 86.11. With the Independent t-test, the p-value of knowledge was 0.000 <0.05. There is an Effect of the Animation Video About the PPIA Program on the Knowledge of Pregnant Women in Keru Village, the Working Area UPT of ​​the Sedau Community Health Center.